2005
DOI: 10.1016/j.cub.2005.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Single Units in the Pigeon Brain Integrate Reward Amount and Time-to-Reward in an Impulsive Choice Task

Abstract: The reported activity was modulated by the temporal devaluation of the anticipated reward in addition to reward amount. Our findings contribute to the understanding of neuropathologies such as drug addiction, pathological gambling, frontal lobe syndrome, and attention-deficit disorders, which are characterized by inappropriate temporal discounting and increased impulsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 43 publications
8
106
1
Order By: Relevance
“…Actually, in appetitive color discrimination tasks, a population of neurons responded to visual cues associated with rewards, irrespective of whether operant peck was required or not [25,52]; so far, however, reliable data are not available as to whether the same ensemble of neurons are responsible for both appetitive and aversive memories. Similar reward-related anticipatory activities have been found in a variety of regions including arcopallium [4] and nidopallium caudolaterale [27,42].…”
Section: Arcopallium and Ventral Striatum Constitute Executive Controsupporting
confidence: 64%
See 2 more Smart Citations
“…Actually, in appetitive color discrimination tasks, a population of neurons responded to visual cues associated with rewards, irrespective of whether operant peck was required or not [25,52]; so far, however, reliable data are not available as to whether the same ensemble of neurons are responsible for both appetitive and aversive memories. Similar reward-related anticipatory activities have been found in a variety of regions including arcopallium [4] and nidopallium caudolaterale [27,42].…”
Section: Arcopallium and Ventral Striatum Constitute Executive Controsupporting
confidence: 64%
“…Furthermore, tract tracing studies [13,51,53] revealed that AI has massive descending projections to the midbrain tegmentum and optic tectum, quite different from the mammalian amygdala. When viewed solely from a functional standpoint, AI might be a part of nidopallium -ventral pallium complex involved in the mnemonic and executive control [14,15,19,27]. It is required to develop a common set of tasks and experimental procedures, so the data obtained in different brain areas can be systematically compared.…”
Section: Consumption Time Arcopallium and Cost Aversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroanatomical studies showed the NCL to receive multimodal input from all secondary sensory areas of the forebrain (Leutgeb, Husband, Riters, Shimizu, & Bingman, 1996), to project to telencephalic motor output structures as well as to the basal ganglia (Kröner and Güntürkün, 1999), to be innervated by dopaminergic fibers from midbrain cell groups A8 -A10 (Metzger, Jiang, Wang, & Braun, 1996), and to be characterized by a high density of dopamine D 1 receptors (Schnabel et al, 1997). Physiological studies demonstrated that single units in the NCL code for the upcoming reward (Kalt, Diekamp, & Güntürkün, 1999), bridge the delay between stimulus and response by high sustained activity levels (Diekamp, Kalt, & Güntürkün, 2002), and code for the subjective reward value of a reinforcer (Kalenscher et al, 2005). Neurochemical analyses showed that relative (Divac, Mogensen, & Björklund, 1985) and absolute concentrations of catecholamines (Karakuyu, Diekamp, & Güntürkün, 2003) as well as the relation of different dopamine metabolites (Bast, Diekamp, Thiel, Schwarting, & Güntürkün, 2002) matched the data from the mammalian PFC.…”
mentioning
confidence: 99%
“…For constant delays but different reward amounts the value of the larger reward, and hence the neural activity to it, should be greater than the value of the smaller reward and the neural activity to it. Kalenscher et al (2005) trained birds on a delayed-reward choice paradigm in which they had a choice between two response keys, one that delivered a small reward (2 sec access to food) after 1.5 sec, and the other that delivered a large reward (4 sec access to food). Initially the delay-to-reward for the large reward was also set at 1.5 sec, and naturally under these circumstances the bird pecked the key that delivered the large reward after 1.5 sec than the key that delivered a small reward after 1.5 sec.…”
Section: Figure 8 the Population Response Profile Of Ncl Memory Cellmentioning
confidence: 99%